Perfil do usuário de crack em tratamento no Hospital Escola Portugal Ramalho na cidade de Maceió/Alagoas - Souza, Edilson de Moura (2013)
In order to describe the profile of crack users who seek treatment at Portugal Ramalho Psychiatric Hospital in Maceió / Alagoas, we conducted a cross sectional study in three wards for addicts from February 2010 to March 2011. It was used for assessment of the severity of dependence the ASI-6 (Addiction Severity Index) and a socio-demographic questionnaire. The sample was composed of 200 subjects. The average age of users studied was 27.9 ± 7.6 years, the predominant ethnicity was mulatto totaling 53.5% of respondents, followed by 20.5% of the blacks. It was observed that 51.5% of the sample never married, 61.0% had only primary education and 26.5% were unemployed and out of labor market. With respect to medical injuries, 16.6% of respondents reported chronic respiratory problems and 13.5% other chronic diseases besides disability associated with vision, hearing, hypertension, diabetes, heart disease, epilepsy, hepatitis, HIV, tuberculosis, cancer and cirrhosis. Psychiatric problems were the most common complaint including sleep regulation and anxiety and depression. Issues arising from the use of alcohol were reported by a large number of respondents, as well as legal barriers associated with the use of crack. About 72% of the subjects reported detention and 66% a history of arrests. Difficulties in relationships with family and friends were reported by 60.2% and 55.3%, respectively. The results of this research can help to support the implementation of public policies for more specific planning preventive actions and effective treatment for this population of users within the public health services.